HIV-1 nef limits communication between linker of activated T cells and SLP-76 to reduce formation of SLP-76-signaling microclusters following TCR stimulation - Abraham, Libin; Bankhead, Peter; Pan, Xiaoyu; Engel, Ulrike; Fackler, Oliver Till (The journal of immunology, 2012)
Signal initiation by engagement of the TCR triggers actin rearrangements, receptor clustering, and dynamic organization of signaling complexes to elicit and sustain downstream signaling. Nef, a pathogenicity factor of HIV, disrupts early TCR signaling in target T cells. To define the mechanism underlying this Nef-mediated signal disruption, we employed quantitative single-cell microscopy following surface-mediated TCR stimulation that allows for dynamic visualization of distinct signaling complexes as microclusters (MCs). Despite marked inhibition of actin remodeling and cell spreading, the induction of MCs containing TCR-CD3 or ZAP70 was not affected significantly by Nef. However, Nef potently inhibited the subsequent formation of MCs positive for the signaling adaptor Src homology-2 domain-containing leukocyte protein of 76 kDa (SLP-76) to reduce MC density in Nef-expressing and HIV-1-infected T cells. Further analyses suggested that Nef prevents formation of SLP-76 MCs at the level of the upstream adaptor protein, linker of activated T cells (LAT), that couples ZAP70 to SLP-76. Nef did not disrupt pre-existing MCs positive for LAT. However, the presence of the viral protein prevented de novo recruitment of active LAT into MCs due to retargeting of LAT to an intracellular compartment. These modulations in MC formation and composition depended on Nef’s ability to simultaneously disrupt both actin remodeling and subcellular localization of TCR-proximal machinery. Nef thus employs a dual mechanism to disturb early TCR signaling by limiting the communication between LAT and SLP-76 and preventing the dynamic formation of SLP-76-signaling MCs.
Gesehen am 22.05.2017